MORPHOMETRIC EVALUATION, BY ULTRASONOGRAPHIC EXAM, OF THE PORTAL VEIN, CAUDAL VENA CAVA AND ABDOMINAL AORTA IN HEALTHY DOGS OF DIFFERENT BODY WEIGHTS - Sartor, Raquel; Maprim, Maria Jaqueline; Takahira, Regina Kiomi (Archives of Veterinary Science, 2010)
<span style="font-size: 10pt; font-family: Arial; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="EN-US">The diameters and areas of portal vein, caudal vena cava and abdominal aorta are useful measurements in dogs. These values can be easily measured by ultrasonographic exam, and variations of normality can be an important indicator of hepatic or extra-hepatic alterations. This study aimed to measure the diameter and areas of portal vein, caudal vena cava and abdominal aorta in healthy dogs, with normal corporal score, divided in groups according to the body weight, and assess whether the data are influenced by animal weight. Thirty dogs were examined and divided into three groups (Group A: ≤ 10 kg Group B: from 10.1 to 20.0 kg; Group C: ≥ 20.1 kg). To measure the diameters and areas of portal vein, caudal vena cava and abdominal aorta, the animal was kept in left lateral decubitus position and the transducer was placed on the right lateral abdominal wall, at approximately the 10th or 11th intercostal space, in the porta hepatis region. The diameters and areas of the portal vein, caudal vena cava and abdominal aorta were significantly lower for dogs in Group A with respect to other groups and the dogs from Groups B and C had similar results with each other. The diameters and areas of the portal vein, caudal vena cava and abdominal aorta may vary with the animal size, and reference values must be specific for small, medium and large dogs.